2021
DOI: 10.1177/0276146720979148
|View full text |Cite
|
Sign up to set email alerts
|

Critiquing a Utopian Idea of Sustainable Consumption: A Post-Capitalism Perspective

Abstract: This paper proposes and critiques the idea of a post-capitalism sustainable consumption utopia to improve the ecological and human wellbeing of the planet. Such a notion can stimulate new imaginative thinking on a future sustainable world not dominated by neoliberalism. It can also strengthen SDG-12: responsible consumption and production. To do so, it examines the influence of pro-environmental self-identity, market-based barriers, and knowledge barriers on sustainable consumption buying, product lifetime ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 71 publications
(148 reference statements)
0
7
0
Order By: Relevance
“…While the luxury market grows, public concern for the environment and climate change is at an all-time high. New approaches are needed to address the ecological problems at the macro-level as detailed in The United Nations (UN) 2030 Agenda for Sustainable Development through the Sustainable Development Goals (Dermody et al 2021). Firms are adjusting their practices to meet social and environmental standards, a critical macromarketing issue (Sheth and Parvatiyar 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the luxury market grows, public concern for the environment and climate change is at an all-time high. New approaches are needed to address the ecological problems at the macro-level as detailed in The United Nations (UN) 2030 Agenda for Sustainable Development through the Sustainable Development Goals (Dermody et al 2021). Firms are adjusting their practices to meet social and environmental standards, a critical macromarketing issue (Sheth and Parvatiyar 2021).…”
Section: Introductionmentioning
confidence: 99%
“…As concerns for global warming and the environment grow, sustainable consumption can minimize the environmental effects of consumption (Ozdamar Ertekin and Atik 2015). Macromarketing scholars have called for a new vision of a sustainable world (Dermody et al 2021). Marketers must consider responsible approaches to producing sustainable products that will build sustainable societies (Sheth and Parvatiyar 2021).…”
Section: Introductionmentioning
confidence: 99%
“…As already suggested by Knopman et al (1999), environmental activists are aware that they can be part of the solution with practices that protect the environment, this recognition being the motivational force that drives them in the search of this solution. Thus, environmental activism can lead individuals to understand ecologically correct consumption as the focus of their decisions (Dermody et al , 2021) and be attracted to sustainable fashion consumption, which is observed in this investigation. And, although not the focus of this study, but considering the presented reference on environmental activism (Knopman et al , 1999; Bianchi and Birtwistle, 2012; Tam and Chan, 2018), it is possible to point out that this type of consumption can be adopted as part of its principles and not as a fad.…”
Section: Discussionmentioning
confidence: 77%
“…In terms of methodology, the majority of the articles reviewed are empirical, suggesting the need for conceptual and theoretical articles to shape thinking in the field (see Dermody et al, 2021). Furthermore, many of the studies adopted traditional marketing theories and frameworks in engaging with the SDGs, whilst, very few studies adopted unconventional theories (e.g.…”
Section: Methodological Approachesmentioning
confidence: 99%